The first report of DNA barcoding of commercially important fish in Nias Islands, Indonesia - MUTIA RAMADHANIATY; VINDY RILANI MANURUNG; KHAIRUNNISA KHAIRUNNISA; FRIYUANITA LUBIS; IPANNA ENGGAR SUSETYA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Ramadhaniaty M, Manurung VR, Khairunnisa, Lubis F, Susetya IE. 2024. The first report of DNA barcoding of commercially important fish in Nias Islands, Indonesia. Biodiversitas 25: 742-753. The Nias Islands are an archipelago in the western part of North Sumatera, encompassed by the Indian Ocean, and have become a hotspot for demersal and pelagic fishes. These geographical conditions endow the waters around Nias with large fishery resources, leading to their frequent utilization as fishing grounds for Sumatera Island and its surrounding areas. This research aimed to identify the commercially important fish species with the highest catch frequency in the waters of Nias, and this identification marked the initial stage of the sustainable utilization of fish resources. The method used was DNA Barcoding using genes targeting the COI Mitochondrial locus. Therefore, 43 samples were collected from several North and South Nias fish landing sites. The obtained species were classified into 3 groups based on the commodity type: demersal fish, pelagic fish, and Choncricthyes. There were 8 species of demersal fish (Caesio caerulaurea, Halichoeres scapularis, Lethrinus ornatus, Mulloidichthys flavolineatus, Parupeneus barberinus, Scarus prasiognathos, Plectropomus leopardus, and Variola albimarginata), displaying genetic distances ranging from 0.002-0.275. Pelagic fish consisted of 5 species, namely Amblygaster clupoides, Caranx ignobilis, Caranx sexfasciatus, Ferdauia ferdau, and Scomberomorus commerson, displaying genetic distances ranging from 0.002-0.267. The next commodities were Chondrichthyes with 9 species (Carcharhinus sealei, Himantura leoparda, Neotrygon kuhlii, Paragaleus randalli, Pateobatis jenkinsii, Rhynchobatus cf laevis, Spyrna lewini, Taeniura meyeni, and Urogymnus granulatus), displaying genetic distance ranging from 0-0.271. This value indicates that migratory species such as chondrichthyes have quite extensive movements so that the genetic distance between species and between populations tends to be low.